2019
DOI: 10.1186/s40981-019-0302-6
|View full text |Cite
|
Sign up to set email alerts
|

Mepivacaine-induced anaphylactic shock in a pregnant woman undergoing combined spinal and epidural anesthesia for cesarean delivery: a case report

Abstract: Background: Anaphylactic shock during pregnancy is a rare but life-threatening event for both the mother and the newborn. Case presentation: A 42-year-old woman, who was pregnant with twins, was scheduled for cesarean delivery under combined spinal and epidural anesthesia. An epidural catheter was placed uneventfully. After spinal anesthesia, the patient exhibited skin symptoms and severe hypotension. The patient was diagnosed with anaphylaxis, and subsequently, treatment was started. Fetal heart rate monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…The American College of Obstetricians and Gynecologists indicates that when anaphylaxis occurs, maternal stability does not guarantee fetal oxygenation. Previous case reports about anaphylaxis in pregnant women demonstrated that 46% of neonates were affected by neurologic adverse effects (12). In this case, both mother and neonate were discharged in healthy conditions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The American College of Obstetricians and Gynecologists indicates that when anaphylaxis occurs, maternal stability does not guarantee fetal oxygenation. Previous case reports about anaphylaxis in pregnant women demonstrated that 46% of neonates were affected by neurologic adverse effects (12). In this case, both mother and neonate were discharged in healthy conditions.…”
Section: Discussionmentioning
confidence: 69%
“…Sripriya et al (10) reported an anaphylaxis reaction due to ranitidine during CS. Takahashi et al (12) reported a case of cesarean delivery under combined spinal-epidural anesthesia that was affected by severe anaphylaxis reaction induced by bupivacaine. In their study, delivery was done after 18 minutes, so the first minute Apgar score was 2, and the neonate was intubated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mepivacaine was used for both local infiltration and LOR in the present study. A case of mepivacaine-induced anaphylactic shock has recently been reported [ 11 ]. Therefore, the use of mepivacaine has a potential risk of an allergic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The study was registered with the University Hospital Medical Information Network Clinical Trials Registry (ID: 000022365). Some of the cases included in this study have already been presented in our previous reports, which had different perspectives from the present study [ 10 14 ].…”
Section: Methodsmentioning
confidence: 96%